Heterogeneous tumor features and treatment outcome between males and females with lung cancer (LC): Do gender and sex matter?. (June 2019) - Frega, Stefano; Dal Maso, Alessandro; Ferro, Alessandra; Bonanno, Laura; Conte, PierFranco; Pasello, Giulia
Highlights: Most risk factors for lung cancer (LC) are linked to patient sex and/or gender. Clinical-pathological and molecular LC features differ between sexes. Men and women could differently benefit from chemo, targeted therapies and ICIs. Sex/gender-related mediators of immune responses may affect outcome of LC patients. Patient gender should be used as stratification factor in future phase III trials. Abstract: Lung cancer (LC) is the leading cause of cancer-related death worldwide, despite a decreasing incidence rate in recent years, especially in men. Most risk factors for LC could be linked to an individual's reproductive system and secondary sex characteristics ('sex-related') and/or to some physical, behavioral and personality traits ('gender-related') peculiar to males rather than females or vice versa. An imbalance of these etiologic factors could explain why some LC features may differ between sexes. For this review, an extended literature data collection was performed, using keywords to identify 'sex/gender' and 'LC'. Differences between genders in LC epidemiology, pathological and molecular characteristics, loco-regional and/or systemic treatments outcome and prognosis were systematically analyzed. The possible predictive role of physio-pathological factors in males and females paves the way for a personalized therapeutic approach, emphasizing the need to include gender as a stratification factor in future clinical trials design.